White Nationalism and Publicness in the United States - Amaya, Hector (Javnost-The Public, 2018)
This is an analysis of the mainstreaming of white nationalism in the USA and its connection to nativism, publicity theory and colonialism. The analysis is set against the backdrop of white nationalist violence in Charlottesville, Virginia, my hometown, and the public persona of Stephen Bannon, the influential adviser to President Trump’s campaign and an intellectual leader of white nationalists in the United States. Using the public debate on speech rights and the right to bear arms in the United States, and the way in which Bannon’s media career has relied on the spectre of violence, the article proposes the need to re-theorise publicity for contemporary life in the USA. I argue that traditional notions of publicness are rooted and depend on troubling fantasies of peaceful communication that hide the violent means by which the state construct the rules of public participation. In the US context, these fantasies are exploited by white nationalists like Bannon, who engage in public dialogue while threatening with armed violence. The fantasies politically sanitise what is coercive, racist and fascist.